Equilibrium analysis of general N-population multi-strategy games for generation-side long-term bidding: An evolutionary game perspective. (10th December 2020) - Cheng, Lefeng; Liu, Guiyun; Huang, Hanqi; Wang, Xiaogang; Chen, Yang; Zhang, Jie; Meng, Anbo; Yang, Ru; Yu, Tao
Abstract: Founded on bounded rationality and limited information, evolutionary game theory can well describe the evolution rule of population behavior and predict individuals' decision-making behavior. Therefore, this paper focuses on the general N -population multi-strategy evolutionary games, and uses them to investigate the generation-side long-term bidding issues in electricity market. First, the long-term equilibrium characteristics of typical two-population and three-population two-strategy evolutionary game scenarios are thoroughly investigated through theoretical analysis and dynamic simulation, where novel relative net payoff parameters are completely defined for these games in engineering. Research shows that the long-term evolutionary stable equilibria are only determined by the relative net payoff parameters, so that an expected evolutionary stable equilibrium can be obtained by adjusting these parameters. Second, the modeling idea of general N -population multi-strategy evolutionary games is elaborated based on replicator dynamics. In the case study, the evolutionary stable equilibrium of generation-side long-term bidding is investigated for a supply-side market involving different generator populations. This case effectively verifies the evolutionary dynamics of the general N -population multi-strategy evolutionary games built in this paper. Lastly, future investigations of evolutionary game theory are prospected. Overall, this paper explores the long-term equilibrium characteristics of the general N -population multi-strategy evolutionary games, which can provide some inspirations and theoretical reference for researches on complex long-term dynamic interactive decision-making problems of group participants with bounded rationality in some relevant fields, especially in the economics, management, and engineering fields. Highlights: Final long-term evolutionary stable equilibria are only determined by defined RNP parameters. An expected evolutionary stable equilibrium can be obtained by adjusting the RNP parameters. The general nPmSEG models are effectively verified by a two-population supply-side bidding case. Some thoughts are provided for studying the decision-making of boundedly rational populations.